2012
DOI: 10.1007/s10843-012-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of geographic diversification on export performance of small and medium-sized enterprises (SMEs)

Abstract: Two alternative diversification strategies-the geographic diversification of export sales and key market concentration-are extensively discussed in management, strategy, entrepreneurship, and economics literature. However, no conclusive evidence currently exists as to how either of these strategies affects the performance of international sales. This paper contributes to a better understanding of geographic diversification as a key dimension of the internationalization process for small and medium-sized enterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 71 publications
1
41
0
1
Order By: Relevance
“…Data Main variables Findings Cieslik et al (2012) 3609 Polish exporting SMEs between 2003 and 2006 Export performance: export sales growth (DV); geographic diversification: number of export markets; export concentration: EU export market versus other export markets; concentration of export sales: % of sales to the largest host country…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Data Main variables Findings Cieslik et al (2012) 3609 Polish exporting SMEs between 2003 and 2006 Export performance: export sales growth (DV); geographic diversification: number of export markets; export concentration: EU export market versus other export markets; concentration of export sales: % of sales to the largest host country…”
Section: Studymentioning
confidence: 99%
“…One there is no relationship between the number of foreign export destinations (markets), and firm performance (Piercy, 1981). Two there are performance benefits for SMEs following a focused export strategy, namely, exporting small export volumes to very few destinations (Cieslik, Kaciak, & Welsh, 2012). Three, there are performance benefits for SMEs following a diversified export strategy, that is exporting larger export volumes to multiple export destinations (Pangarkar, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of Polish exporters, Cieślik et al (2012) concluded that two viable strategies included concentrating on a single market or a more balanced approach where a small number of key markets are targeted in conjunction with penetrating other markets. Yet, a more fine-grained analysis of the performance implications and possibility of curvilinear relationships would be welcome.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Diversification is defined in various manners such as the change in existing composition of product mix or export market destination or spread of product over many sectors (Salomon, 2010;Berthelemy and Chaivin, 2000;Ali et al, 1991). However, the impact of geographic or market and product diversification is still a substantial debatable topic in international trade literature (Jerzy et al, 2012) because the countries that have more diversified export (Horizontal and vertical product) will have stable export revenue and which would lead to long-run growth (Dierk and Felicitas, 2007;Fahim, 2010;Sheila and Michael, 1997;Manuel, 2008). On the contrary, highly concentrated market or product would lead vulnerable condition in export performance and export revenue stream (Federico and Kiichiro, 2003).…”
Section: Introductionmentioning
confidence: 99%